Peningkatan Kompetensi Wirausaha Muda Berbasis Ekonomi Kreatif Melalui Standardisasi Produk - Tajibu, Muhammad Jibril; Mustari, Bakhtiar; Siswadarma, Baso (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2023)
It is important to carry out this PKM activity considering that the government is currently intensively seeking to develop entrepreneurship in society as an opportunity to overcome unemployment by creating jobs. The existence of entrepreneurship education in universities has provided benefits for graduates, but many productive young people in rural areas have not had the opportunity to experience a proper education, so it is very difficult for the businesses they run to develop, let alone penetrate a wide market. For this reason, the main focus of this PKM activity is to provide education regarding the competencies that young entrepreneurs must have in producing and marketing through the creation of quality and national standard products. With this education, it is hoped that young entrepreneurs can have a more advanced mindset by implementing product quality standardization in managing their business which their parents have not done so far. So the emergence of productive young entrepreneurs can be a solution to this problem. For this reason, it is necessary to be prepared by providing entrepreneurial competency education to create creative economy-based products that have national quality standards. Activities are carried out through educational and mentoring methods, with an implementation time of 1 month. The team that will handle it has expertise in economic development of human resources, marketing, entrepreneurship, and knowledge and experience in the fields of national standardization and product quality. The visible result is an increase in partners' knowledge regarding product standards to be able to compete in a wider market, as evidenced by the arrangement of production space and the use of national standard materials.